Determinan Return Saham Industri Otomotif dan Komponen yang Terdaftar di BEI - Jaja Suteja; Patrisius Seran (Faculty of Economics and Business, University of Pasundan, 2015)
This study is aimed at determining the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), Net Profit Margin (NPM), inflation, exchange rates, and interest rates on stock return of Automotive Industry and its Components. The method used is in this research is data panel regression and the period of research is from 2009 to 2013. The result showed that the ROE, DER, NPM, inflation, exchange rates, and interest rates affect the stock return of Automotive Industry and its Components. Partially, ROE and inflation positively affect the stock return, while the exchange rates and interest rates negatively affect the stock return. The rest, DER and NPM have no effect on stock return.